Exploring the Influence of Instructional Leadership on Service Quality of Vocational Public School Teachers - Intan Nur Anggraeni; Masduki Ahmad; Rugaiyah (South Sulawesi Education Development (SSED), 2024)
Teachers, as the main actors in the education process in schools, need to pay attention to the quality of services they provide to students as their primary customers. In achieving the expected quality of service, the principal's leadership plays an important role as the driver and determinant of school policy direction. This study aims to analyze and explore the extent of the influence of instructional leadership on improving the quality of service of Vocational School teachers. This research uses a quantitative approach with a survey method, product-moment correlation, and simple linear regression analysis techniques. The data in the study were obtained through a questionnaire with a research sample of 112 teachers selected randomly through a simple random sampling technique. The results showed that instructional leadership has a positive and significant effect on the quality of teacher services, with a percentage of the influence being 42.9%, which means a moderate correlation. This provides information that if instructional leadership by school principals increases, the quality of teacher services in schools will also increase. This study implies that principals need to allocate particular time to motivate and facilitate teachers to improve the quality of their services, dialogue with teachers, build effective communication, conduct adequate supervision, and monitor the progress of student learning outcomes optimally through teachers.